Parceling the globe philosophical explorations in globalization, global behavior, and peace - Poe, Danielle; Souffrant, Eddy M., 1959- (Value Inquiry Book Series, 2008)
Parceling the Globe is a study in the processes of global democracy. It offers an early answer to the question regarding our responsibility to others. Through its organization, it presents a partial understanding of the globalization process. It determines the range of global behaviors and articulates the prospects for peace in a globalizing environment.